Pathogenesis of gall stones in Crohn's disease: an alternative explanation. - Hutchinson, R (1994)
The increased prevalence of gall stones in Crohn's disease is thought to be related to depletion of the bile salt pool due either to terminal ileal disease or after ileal resection. This study was designed to examine whether this hypothesis is correct and explore alternative explanations. Two hundred and fifty one randomly selected patients (156 females, 95 males, mean age 45 years) were interviewed and screened by ultrasonography to determine the prevalence of gall stones in a large population of patients with Crohn's disease. Sixty nine (28%) patients had gall stones proved by ultrasonography (n = 42), or had had cholecystectomy for gall stone disease (n = 27). The risk factors for the development of gall stones including sex, age, site, and duration of disease, and previous intestinal resection were examined by multivariate analysis. Age and duration of disease were positive risk factors for gall stones and were covariables. The site of disease and of previous intestinal resection did not predispose to gall stones. Previous surgery was an independent risk factor for the development of gall stones, the risk increasing with number of laparotomies. It is suggested that mechanisms other than ileal dysfunction may predispose to gall stones. Postoperative gall bladder hypomotility with biliary sludge formation may be precursors of gall stone formation in patients with Crohn's disease.